Meningkatkan Tanggung Jawab Sosial Siswa Kelas VIII Melalui Layanan Bimbingan Kelompok - Nisa, Ummi Farikhatun; Supriyo, Supriyo; Mugiarso, Heru (Universitas Negeri Semarang, 2012)
The purpose of this research was to determine the efforts and success in improving students' social responsibility through group counseling services. Type of research used action research. Subjects were 12 students who had low social responsibility and being. Data collection technique used were psychological scales and observation. Data analysis techniques used are non-parametric statistics with the Wilcoxon test. Based on the calculations for the Wilcoxon test, a small amount of levels or Z value was 78.0. While Ztabel for n = 12 with an error level of 5% value is 14. So Z 78.0> 14.0 Ztabel or imply hypothesis accepted. These results demonstrate social responsibility of students prior to obtaining counseling services group at 51.93% (low). After following the guidance services at 81.51% (high). Conclusions from this research is a social responsibility to the students of class VIII SMP Putra Bangsa Bantarkawung increase after getting tutoring services group.